Left ventricular mural thrombus and dual coronary embolization associated with hyperthyroid cardiomyopathy and atrial fibrillation: a case report - Guohui Liu; Ping Yang; Yuquan He (BMC Cardiovascular Disorders, 2017)
Abstract Background The majority of acute myocardial infarction (AMI) events are caused by thrombotic occlusion of the coronary artery, secondary to atherosclerotic plaque erosion or rupture. However, coronary embolism (CE), while rare, is being increasingly recognized as an important cause of AMI. We present the case of a patient with multi-site coronary artery embolization associated with hyperthyroid-related cardiomyopathy and atrial fibrillation. Case presentation A 49-year-old female with a history of hyperthyroidism and atrial fibrillation (AF) was admitted to our hospital presenting with right upper limb pain and swelling. Initial transthoracic echocardiography demonstrated left ventricular apical mural thrombi and hyperthyroidism-induced cardiomyopathy. On the eighth day after admission, the patient developed sudden onset of severe chest pain and evidence of acute myocardial infarction (AMI). Emergency coronary angiography revealed multi-site coronary embolization of the left anterior descending artery and a large diagonal branch. Despite emergency thrombo-aspiration and balloon angioplasty, the patient went into ventricular fibrillation, from which she did not recover. Conclusion Although rare, a fatal case of left ventricular thrombus and dual-vessel coronary embolism associated with hyperthyroid cardiomyopathy and atrial fibrillation is reported.